PERAN MUSEUM ARMA DAN MUSEUM BURUNG BALI DALAM PEMBERDAYAAN BUDAYA DAN MASYARAKAT LOKAL - I Made Mardika (Universitas Warmadewa, 2018)
[Title: The Roles of Museum Arma and Museum Burung Bali in Empowering the Culture and Local Society] This article aims to identify roles of Museum Arma and Museum Burung Bali in empowering the culture and local society and to interpret its meaning. The research model is qualitative research. The data collection were done by observation technique, deep interview and documentation, and the data analysis were done inductively. The result shows two ways in empowering the culture and local society. Museum Arma empowers them by museum integrated management model and living museum. Museum Burung Bali empowers them by employing local artist to make collection, souvenirs and traditional Balinese dance performances. The process can be interpreted as local cultural response towards global culture, the deconstructive strategy towards inversion from outside to inside, and the capitalization towards local culture. The conclusion is both museums have roles in empowering the culture and local society towards certain strategies reflexing the meaning of cultural response, local culture improvement, and cultural capitalization.